EVALUASI PROGRAM PENILAIAN PENCAPAIAN KOMPETENSI I (PPK I) DENGAN MODEL CONTENT, INPUT, PROSES, DAN PRODUCT (CIPP) - Sugandini, Wayan; Dewi Tarini, Wayan; Espana Giri, Ketut; Nik Armini, Luh (Jurnal Imiah Pendidikan dan Pembelajaran, 2018)
The purpose of this study was to evaluate the PPK I program in order to identify its effectiveness. The method used in this study was the Context, Input, Process, and Product (CIPP) model of Stufflebeam. This research was conducted in the Midwifery 3 diploma program. Research subjects included 13 lecturers, and 2 education staff. Data collection was done by filling out questionnaires by the subject, as well as filling out the interview sheet. The data obtained were analyzed by percentile quantitative analysis. The results showed that: 1) 78.21% of the Context dimension supported the PPK I program, 2) 74.8%, the Input dimension supported the PPK I program, 3) 82%, of the Process dimension supported PPK I and 4 programs) 78%. Product dimensions support the PPK program I. From the results of the above research, it can be concluded that the Context dimension of the category of effectiveness is sufficient, the dimensions of the input category of effectiveness are sufficient, the dimensions of the Process category are high, and the dimensions of the category of effectiveness are sufficient. Keywords: Evaluation, CIPP, PPK I